Current issues in project analysis for development - Weiss, John; Potts, David (Cheltenham Edward Elgar Publishing Ltd., 2012)
Summary: Project analysis techniques have been applied in the assessment of development projects for over fifty years, where poorly designed and appraised projects can waste scarce resources. This study examines the continued relevance of this approach, assesses methodological developments over this period and investigates current practical problems in the application of these techniques. This major work brings together authors with experience of both academic and operational project work to focus on issues such as the shadow exchange rate, the shadow wage, the discount rate, assessment of poverty impact and risk, as well as problems relating to specific sectors covering environmental projects, transport, education and health. There are also general chapters on the experience of semi-input-output based estimation of shadow prices and the relevance of shadow pricing techniques to the context of developed economies in the EU. An overview by the editors sets out the evolution of the literature and highlights current issues. The general conclusion is that project analysis techniques remain relevant albeit within a very different development context to that in which they were originally envisaged to be applied. With new perspectives on key economic parameters, this book will appeal to academics working on development, officials involved with project aid programmes, postgraduate students of development and professional economists working on development projects
1. Editors' Introduction / David Potts and John Weiss --
2. Estimating a Shadow Exchange Rate / Elio Londero --
3. Shadow Wages Rates in a Changing World / David Potts --
4. Semi-Input-Output Methods of Shadow Price Estimation: Are They Still Useful? / David Potts --
5. Projects and the MDGs: Estimating Poverty Impact / Manabu Fujimura --
6. Projects and Risk / John Weiss and Keith Ward --
7. Discounting: Does it Ensure Intergenerational Equity? / Erhun Kula --
8. Environmental valuation / P.B. Anand --
9. Assessing the Benefits of New or Improved Roads / Chris Nash --
10. Project appraisal in Health: Cost Effectiveness Approaches / John Weiss --
11. Measuring Benefits from Education / David Potts --
12. Cost-Benefit Analysis traditions : the approach of EU Regional Policy / Massimo Florio and Silvia Vignetti --
Summary from the Back cover of the book
Includes bibliographical references (p.249-278) and index.
Keywords: Economic development; ECONOMIC DEVELOPMENT; PROJECTS; PROJECT EVALUATION; DEVELOPING COUNTRIES